INADIA OMARA'S COMMUNICATION STYLE ON THE YOUTUBE CHANNEL TO ATTRACT VIEWERS' INTEREST - Annisa Br Sembiring; Dedi Sahputra (RADJA PUBLIKA, 2025)
This study aims to describe the verbal and nonverbal communication styles used by Nadia Omara in delivering horror content on her YouTube channel and to analyze their impact on viewers' interest. The research employs a descriptive qualitative method, with data collected through content observation, interviews with active viewers, and documentation. The findings indicate that Nadia Omara's distinctive communication style—combining a personal touch, poetic language, empathy, supportive visual and audio elements, and storytelling techniques—successfully builds emotional closeness with the audience. This approach not only makes the content more engaging and easier to understand but also enhances audience engagement and sustains their interest in following her channel. The study offers theoretical contributions to mass communication studies and practical implications for digital content creators in developing effective communication strategies.